Postępowanie z wniosku o udostępnienie informacji publicznej przetworzonej - Korzeniowska-Polak, Agnieszka (Kwartalnik Prawa Publicznego, 2012)
The notion of ‘processed information’ has been used merely on a single occasion by the Polish legislator, and in only one provision of the Act on the access to information held by public authorities. Art. 3 section 1 of the Act states that access to information held by public authorities may be granted only in so far as it is of particular significance for the public interest. The legislator did not, however, mention the notion in any other provision, neither did they specify its definition nor indicate the entity in charge of proving the relationship between obtaining information by an applicant and its qualified significance for the public interest. The legislator also omitted to indicate the entity in charge of assessment whether making information available to the applicant actually is of particular significance for the public interest, and to determine legal consequences which should result from a failure to prove the same. Lack of clear and unambiguous legal basis pertaining to making processed information available has been compensated for by jurisprudence and views established by legal commentators. Some of them have been contested in this feature and analysis have been made of the procedure related to implementation of the right of access to processed information held by public authorities – a standpoint largely omitted in literature so far. While considering a possibility to apply provisions of the code of administrative procedure to proceeding on a request for information held by public authorities, effort has been made to establish a proper legal basis to require an applicant to prove a premise of particular significance for the public interest, vital elements of such a request have been identified as well as legal forms of conclusion of a proceeding on a request for processed information held by public authorities have been indicated.